Parkinson Activity Scale: Cross‐cultural adaptation and reliability of the Brazilian version. Issue 1 (24th January 2014) - Santos, Mariana P; Ovando, Angélica C; Silva, Bruna A; Fontana, Samanta RCB; do Espírito Santo, Caroline C; Ilha, Jocemar; Swarowsky, Alessandra
<x xml:space="preserve">Abstract</x> Aim Following the substantial growth of the elderly population in Brazil, there has been an increase in cases of Parkinson's disease (PD), which raises the need for reliable and culturally adapted scales specific to the disease. The Parkinson Activity Scale (PAS) was developed in order to assess the activity level of people with PD through tasks related to mobility. The aims of the present study were to translate the cross‐cultural adaptation of the PAS into Brazillian Portuguese and analyze its reliability during the "on" phase of PD. Methods A total of 25 patients with PD participated in the study. The intrarater reliability was evaluated using a test–retest design with a 1‐week interval. Results The interrater reliability was tested twice on the same day by two different raters. The intraclass correlation coefficient (ICC), and the Bland and Altman plots were calculated to examine the test–retest and interrater reliabilities for total score of the PAS, whereas the weighted Kappa (Wk) was used to assess interrater agreement. The interrater ICC was 0.89 and Wk was 0.65 for the total score. For intrarater reliability, the total score ICC was 0.88. Conclusions The present study suggests that the Brazilian version of the PAS is a reliable instrument for the assessment of mobility in elderly patients with PD. Geriatr Gerontol Int 2015; 15: 89–95.